ЗАКОНОДАВЧЕ ОБМЕЖЕННЯ ЕКОНОМІЧНОГО ФУНКЦІОНУВАННЯ ЦЕРКВИ І РЕЛІГІЙНИХ ОРГАНІЗАЦІЙ В РАДЯНСЬКІЙ УКРАЇНІ 1920-Х РОКІВ (Zaporizhzhia Historical Review, 2021)
The Usase of working and legal regulations for influence over internal church process by party and state authorities of the Ukrainian Soviet Socialist Republic in 1920 ies are in the focus of the article. The theorists of the Soviet Ukrainian law worked out law standards which implementation led to deprivation of church and religious communities of: 1) organizational and legal unity in the form of juridical person and 2) ability to give the signs of “ formal and legal compulsion” with respect both to the members of these communities and their sympathizers